Incidence and predictors of eosinophilic myocardial hypersensitivity in patients receiving home dobutamine. (14th October 2021) - Dagan, M; Lankaputhra, M; Yeung, T; Tee, S.L; Bader, I; Easton, K; Linton, A; McLean, C; Taylor, A; Bergin, P; Kaye, D.M; Leet, A; et al.
Abstract: Background: Home inotropes are utilised in those with end-stage heart failure as a bridge to cardiac transplantation. The use of intravenous dobutamine has been linked to cases of eosinophilic myocardial hypersensitivity (EMH), however, little is known about incidence and predictors. Purpose: We sought to examine the incidence and possible predictors of eosinophilic myocardial hypersensitivity in a cohort of patients on home inotrope therapy at a cardiac transplant centre. Methods: Patients enrolled in the home inotrope program with progression to heart transplantation or ventricular assist device (VAD) with available myocardial tissue for histopathology, from January 2000 to May 2020 were included. EMH was defined by a pathologist reporting eosinophilic infiltrate with hypersensitivity on myocardial histopathology. Results: From a cohort of 74 patients, 58% (43) were on dobutamine and 42% (31) were on milrinone. There were zero cases of EMH in those on milrinone. EMH was identified in 14% (6/43) of patients receiving dobutamine. In the dobutamine cohort, the mean age was 52-±12 years, with 22% being female. Non-ischaemic dilated cardiomyopathy encompassed 62%, the remaining 38% were ischaemic cardiomyopathy. Median dobutamine dose (250 [200–282] mcg/min vs. 225 [200–291] mcg/min) and duration of therapy (41 [23–79] days vs. 53 [24–91] days) were similar between those with and without EMH. Rates of known allergy (27% vs. 33%) and asthma (1 patient in each group) were also similar between those with and without EMH. Those with EMH had a median peak eosinophil count of 0.40×10 9 /L (IQR 0.21–0.66×10 9 /L) compared to a peak of only 0.10×10 9 /L (IQR 0.06–0.29×10 9 /L) in the non-EMH cohort. There was a significant difference in the change in absolute eosinophil count between groups; over the duration of dobutamine therapy the median change in eosinophil count was 0.31×10 9 /L (IQR 0.21–0.59×10 9 /L) in the EMH group compared to 0.03×10 9 /L (IQR 0.00–0.14×10 9 /L) in the non-EMH cohort (p=0.02). Peak C-reactive protein was similar between groups (42±46mg/L vs. 44±45mg/L). Mean left ventricular ejection fraction (LVEF) reduced from 19% (±7%) to 17% (±2%) in those with EMH, while LVEF increased from 20% (±7%) to 22% (±9%) in non-EMH patients (Figure 1), p=NS. Re-presentation with heart failure requiring hospitalisation occurred in 83% in the EMH group compared to only 59% in the non-EMH group (p=0.26). The majority of patients with EMH (83%) required VAD as bridge to transplant, compared to only 41% of non-EMH (p=0.05). Conclusion(s): EMH occurred in 14% of patients receiving home dobutamine. Patients who developed EMH were more likely to require escalation in treatment to VAD as a bridge to heart transplant. In patients receiving dobutamine a reduction in LVEF, hospitalisation with decompensated heart failure and rising eosinophil count should prompt physicians to consider EMH. Funding Acknowledgement: Type of funding sources: None.